Web-Based Geographic Information System on the Covid-19 Vaccine in Banda Aceh City - Muzailin Affan; Fadhil Hidayatullah; Dahlan (Nur Science Institute, 2022)
The influence of the development of information technology makes it easier for anyone to share and obtain information, one of which is information regarding the COVID-19 vaccination. The RI Ministry of Health has provided information regarding COVID-19 vaccination in the form of a WEBGIS, however, the website still has several deficiencies such as the unavailability of data on COVID-19 vaccination achievements per sub-district and village, does not provide information regarding the distribution of vaccination locations and routes to vaccination locations, and does not provide a form for registration of vaccinations. Therefore, we need a system that can overcome these deficiencies, especially for the City of Banda Aceh. This WEBGIS development uses Laravel as a Framework, Leaflet as a library and MariaDB as a database. The COVID-19 Vaccination WEBGIS for Banda Aceh City can provide information on vaccination achievements per sub-district and village in the form of graphs and thematic maps which are grouped into 3 color classes according to vaccination achievements. In addition, this WEBGIS also provides information on the distribution of vaccination locations along with routes to these locations. This WEBGIS also makes it easier for people who want to vaccinate because a form is available to register for vaccination. The Health Office also gets convenience in terms of data management and printing of vaccination data. WEBGIS has carried out usability testing on users. This usability test involved 30 respondents using 30 questions from the USE (Usefulness, Satisfaction, and ease of use) Questionnaire method which were divided into 4 sections. The results of this WebGIS test obtained an average score of 88.67%, which means that this WEBGIS is included in the very decent category.